Prospects of Flax Fibre Cultivation - Chaudhary, Babita; Tripathi, M. K.; Pandey, S.K.; Bhandari, H. R.; Meena, D. R.; Prajapati, S.P. (Indian Farming, 2015)
In India linseed has been under cultivation from prehistoric times. There is no acreage under flax type varieties. Some efforts were made to grow flax in India in 19 th century but its cultivation did not pick up. Adequate research efforts were also not made in the country for developing improved varieties and production technologies. Availability of quality seed and scotching machine, retting and scotching operations are some of the major constraints in cultivation in the country. Although flax has many advantages as a fibre crop, its overwhelming disadvantage is the amount of labor, skilled and otherwise, required from sowing to harvest. Processing flax is an extremely labor-intensive process that can help in providing skilled and unskilled employment in the country. With the available technology, farmers can grow flax fibre successfully.